Технологія забезпечення надійності пружних елементів машин - Кукляк, М. Л.; Кук, А. М. (Видавництво Національного університету «Львівська політехніка», 2001)
Is shown, that the necessary level of machines reliability in conditions of cyclic loading can be reached by increase of the materials durability characteristics with the mechanical, thermal, thermomechanical and other kinds of complex hardening. For creation of appropriate resistance to this loading it is necessary to ensure the high borders of proportionality and weariness.